2014
DOI: 10.1007/s12035-014-8709-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic CSF Prion Seeding Efficiency in Humans with Prion Diseases

Abstract: The development of in vitro amplification systems allows detecting femtomolar amounts of prion protein scrapie (PrPSc) in human cerebrospinal fluid (CSF). We performed a CSF study to determine the effects of prion disease type, codon 129 genotype, PrPSc type, and other disease-related factors on the real-time quaking-induced conversion (RT-QuIC) response. We analyzed times to 10,000 relative fluorescence units, areas under the curve and the signal maximum of RT-QuIC response as seeding parameters of interest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 29 publications
(34 reference statements)
11
86
0
3
Order By: Relevance
“…From this limited number of CSF samples, we have achieved an overall sensitivity of between 85.7% and 100% and a specificity of 100%. This compares well with a previous intralaboratory study, which had fewer participants and reported a sensitivity of 85% and a specificity of 99% 10. The complete concordance between laboratories demonstrates that CSF RT‐QuIC is adaptable to different laboratory instrumentation and different types of rPrP.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…From this limited number of CSF samples, we have achieved an overall sensitivity of between 85.7% and 100% and a specificity of 100%. This compares well with a previous intralaboratory study, which had fewer participants and reported a sensitivity of 85% and a specificity of 99% 10. The complete concordance between laboratories demonstrates that CSF RT‐QuIC is adaptable to different laboratory instrumentation and different types of rPrP.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that CSF samples from sCJD patients with longer disease durations may have lower seeding efficiency10; however, this effect was not seen in the second ring trial, where the CSF from an sCJD patient with a disease duration of 26 months was identified by RT‐QuIC by all laboratories. All the laboratories that participated in the first ring trial used the same source and type of rPrP and either Optima or Omega BMG LABTECH instrumentation, and demonstrated high levels of accuracy and agreement between laboratories.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the low specificity of p-tau, its incorporation in the p-tau/tau ratio leads to an improved clinical accuracy compared to individual measurements, especially for the discrimination between sCJD and AD cases [9,16]. Indeed, clinical accuracy of the p-tau/tau ratio has been recently reported to be in the range of the RT-QuIC method [9,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Certain studies have shown that the sensitivity of 14-3-3 protein for detecting CJD varies for different CJD genotypes: From 57% in MV2 to 100% in MV1 and VV1 cases, with a specificity from 84 to 95% (27,28). However, the level of 14-3-3 protein varies over time and may not be detectable at certain time-points in certain patients (29). In the present study, the 14-3-3 protein test in the CSF was ~67% positive, as the first patient (M/M type) was negative.…”
Section: Discussionmentioning
confidence: 99%